Setting Occupational Exposure Limits for Genotoxic Substances in the Pharmaceutical Industry - Lovsin Barle, Ester (Toxicol Sci, 2016)
In the pharmaceutical industry, genotoxic drug substances are developed for life-threatening indications such as cancer. Healthy employees handle these substances during research, development, and manufacturing; therefore, safe handling of genotoxic substances is essential. When an adequate preclinical dataset is available, a risk-based decision related to exposure controls for manufacturing is made following a determination of safe health-based limits, such as an occupational exposure limit (OEL). OELs are calculated for substances based on a threshold dose-response once a threshold is identified. In this review, we present examples of genotoxic mechanisms where thresholds can be demonstrated and OELs can be calculated, including a holistic toxicity assessment. We also propose a novel approach for inhalation Threshold of Toxicological Concern (TTC) limit for genotoxic substances in cases where the database is not adequate to determine a threshold.